Transformational Leadership and Project Success: The Roles of Social Capital and Self-Efficacy - Raza, Tahir; Ali, Syed Atif; Majeed, Muhammad Ussama (Universiti Utara Malaysia Press, 2024)
Transformational leaders must constantly monitor their environments to identify and develop significant internal and external exposure to multiple points of view. Transformational leaders serve as role models for bridging organizational boundaries and proactive outreach to external stakeholders to communicate information, develop inter-organizational cooperation, establish coalitions, and harness resources. The major goal of this article is to examine the dynamics that drive organizational project success, specifically the impact of transformational leadership on external and internal social capital in management teams. This research analyzed transformational leadership and project success relationships in Pakistan’s construction industry setting along with the moderating role of the project manager subordinate’s social capital and the mediating role of the project manager subordinate’s self-efficacy. The data were collected from196 subordinates of project managers of different private organizations. Data were examined through correlation, regression, and the Hayes model through SPSS. According to the results, transformational leadership is positively associated with project success and substantially associated with social capital. Additionally, self-efficacy is positively associated with transformational leadership and project success, and it mediates the relationship between transformational leadership and project success. Social capital moderates the relationship between transformational leadership and project success, according to additional findings. This study sheds light on the relationship between transformational leadership and self-efficacy in the context of project success.